Evaluation of Benefits of Irrigation Gang Canal (Rajasthan) - Planning Commission (Planning Commission, 1958)
The Ganga canal named after his Highness, Maharaja Sir Ganga Singh of Bikaner to whose imagination the canal owes its origin, was taken up for construction towards the end of 1925 and formally opened by the then Viceroy at Shivpur on 26th October, 1927. It is said that soon after the Maharaja’s assumption of power, the State had to face a severe famine in the year 1899 which took a heavy toll of life, both human and bovine. The tragedy left a deep impression on the mind of the young ruler who in an attempt to avert repetition of such a catastrophe ceaselessly strove to organise artificial means of irrigation. This effort bore fruit over a period of nearly three decades.
Research Programmes Committee Planning Commission
Research Programmes Committee Planning Commission